Fornix Stimulation Induces Metabolic Activity and Dopaminergic Response in the Nucleus Accumbens - Shin, Hojin; Lee, Sang-Yoon; Cho, Hyun-U; Oh, Yoonbae; Kim, In Young; Lee, Kendall H.; Jang, Dong Pyo; Min, Hoon-Ki (Frontiers in Neuroscience, 2019)
The Papez circuit, including the fornix white matter bundle, is a well-known neural network involved in multiple limbic functions such as memory and emotional expression. We previously reported a large animal study of deep brain stimulation (DBS) in the fornix that found stimulation-induced hemodynamic responses in both the medial limbic and the corticolimbic circuits on functional resonance imaging (fMRI) and evoked dopamine responses in the nucleus accumbens (NAc), as measured by fast-scan cyclic voltammetry. The effects of DBS on the fornix are challenging to analyze given its structural complexity and connection to multiple neuronal networks. In this study, we extend our earlier work to a rodent model wherein we characterize regional brain activity changes resulting from fornix stimulation using Fludeoxyglucose (18F-FDG) micro positron emission tomography (PET) and monitor neurochemical changes using fast scan cyclic voltammetry (FSCV) with pharmacological confirmation. Both global functional changes and local changes were measured in a rodent model of fornix DBS. Functional brain activity was measured by micro PET, and the neurochemical changes in local areas were monitored by FSCV. Micro PET images revealed increased glucose metabolism within the medial limbic and corticolimbic circuits. Neurotransmitter efflux induced by fornix DBS was monitored at NAc by FSCV and identified by specific neurotransmitter reuptake inhibitors. We found significant increase in the metabolic activity in several key regions of the medial limbic circuits and dopamine efflux in the NAc following fornix stimulation. These results suggest that electrical stimulation of the fornix modulates the activity of brain memory circuits, including the hippocampus and NAc within dopaminergic pathway.